Richard Tawney and the First World War - Howson, Peter (International journal for the study of the Christian church, 2023)
This article is based on a paper that was delivered in September 2022 as part of a symposium organised by the Henry Scott Holland Trust to mark the centenary of the Henry Scott Holland lecture. That lecture had been given by R.H. Tawney. This paper explores his engagement with the First World War as a volunteer soldier and a member of the Church of England.